2023
DOI: 10.1007/s44202-023-00066-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of face masks and sunglasses on attractiveness, trustworthiness, and familiarity, and limited time effect: a Japanese sample

Abstract: Many studies conducted after the COVID-19 pandemic have examined the relationship between changes in social traits, such as attractiveness and wearing face masks. However, most studies examine the effect of wearing face masks at a single time point, and the time effect is not known. Additionally, few studies address wearing sunglasses, another facial occluding item. This study examined the effects of facial occluding (unoccluded face, face masks, sunglasses, or both) on perceived attractiveness, trustworthines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Notably, rather inconsistent findings have been reported so far. Whereas several studies reported bolstered positive impressions (e.g., Castelli et al, 2022 ; Di Crosta et al, 2023 ; Guo et al, 2022 ; Oldmeadow & Koch, 2021 ; Olivera-La Rosa et al, 2020 ), other studies did not observe a similar pattern (e.g., Bennetts et al, 2022 ; Biermann et al, 2021 ; Grundmann et al, 2021 ; Takehara et al, 2023 ; Twele et al, 2022 ). Cultural and individual difference factors can to a large extent account for this variability (see Leder et al, 2022 ; Swain et al, 2022 ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Notably, rather inconsistent findings have been reported so far. Whereas several studies reported bolstered positive impressions (e.g., Castelli et al, 2022 ; Di Crosta et al, 2023 ; Guo et al, 2022 ; Oldmeadow & Koch, 2021 ; Olivera-La Rosa et al, 2020 ), other studies did not observe a similar pattern (e.g., Bennetts et al, 2022 ; Biermann et al, 2021 ; Grundmann et al, 2021 ; Takehara et al, 2023 ; Twele et al, 2022 ). Cultural and individual difference factors can to a large extent account for this variability (see Leder et al, 2022 ; Swain et al, 2022 ).…”
Section: Discussionmentioning
confidence: 96%
“…Several studies found an increased positive perception of faces wearing a face mask as compared to faces without the mask (Castelli et al, 2022 ; Di Crosta et al, 2023 ; Guo et al, 2022 ; Oldmeadow & Koch, 2021 ; Olivera-La Rosa et al, 2020 ). Other studies, however, reported no significant effect, mixed findings, or even an opposite pattern (i.e., more positive ratings for faces without the mask; Bennetts et al, 2022 ; Biermann et al, 2021 ; Grundmann et al, 2021 ; Takehara et al, 2023 ; Twele et al, 2022 ). This makes it important to highlight some overarching factors that might shape the strength, and, possibly, the direction of the effects.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of these studies, though, have been mixed. Of 15 papers published between 2020 and 2023, six found masked faces were rated higher in trustworthiness compared to unmasked faces ( Di Crosta et al, 2023 ; Guo et al, 2022 ; Kawakami et al, 2023 ; Lau, 2021 ; Oldmeadow & Koch, 2021 ; Olivera-La Rosa et al, 2020 ), four found masked faces were less trustworthy ( Biermann et al, 2021 ; Bylianto & Chan, 2022 ; Gabrieli & Esposito, 2021 ; Takehara et al, 2023 ), and five found no differences or were inconclusive ( Bennetts et al, 2022 ; C. Twele et al, 2022 ; Cannito et al, 2022 ; Grundmann et al, 2021 ; Oliveira & Garcia-Marques, 2022 ). The variability in results may stem from differences in methodology, as well as contextual factors that influence the meanings given to mask wearing ( Wang et al, 2023 ).…”
mentioning
confidence: 99%
“…They found no difference in trustworthiness between masked and unmasked faces and there was no effect of time. Takehara et al (2023) examined trustworthiness ratings of masked and unmasked faces in mid-2020 and again in September 2022, using Japanese samples. Masked faces were rated lower in trustworthiness than unmasked faces, and there was no difference in this effect across the two time points.…”
mentioning
confidence: 99%